(untitled) - Rubin, Barry; Barry Rubin; Judith Colp Rubin (New York, 2002)
Over many decades, radical forces in the Middle East have changed and evolved, yet their basic outlook and anti-Western views have remained remarkably consistent. Barry Rubin and Judith Colp Rubin have assembled nearly one hundred key documents, charting the evolution of radical Middle East movements, their anti-Americanism, and Western policy response. The buildup to the battle between a world superpower and Middle East revolutionaries is brought dramatically to life. Among the documents included are the charters of such organizations as Hizballah, Hamas, and World Islamic Front; speeches by Syrian president Hafiz al-Asad and former Iraqi president Saddam Hussein; al-Qa'ida recruitment materials; and terrorist training manuals. The book also shows and analyzes the often conflicting and deeply conflicted responses to September 11 by journalists, clerics, and activists in the Arab world
Keywords: Terrorism; Terrorism; Terrorism